Descriptive-comparative study of aerobic performance parameters between soccer and futsal athletes. - Bruno Manfredini Baroni (Revista Brasileira de Cineantropometria e Desempenho Humano, 2011)
Although soccer and futsal are sports with similar motor actions, the differences in size and match dynamics result in distinct physiological requirements. The objective of this study was to evaluate and compare parameters of aerobic capacity between professional soccer and futsal athletes. A total of 553 ergospirometric evaluations were performed: 367 soccer players (32 goalkeepers, 335 on-court players) and 186 futsal athletes (22 goalkeepers, 164 on-court players). The results were analyzed separately for each modality (comparison between goalkeepers and on-court players) and compared between soccer and futsal athletes. Soccer and futsal goalkeepers presented lower maximal oxygen uptake (VO2max), second ventilatory threshold (VT2), and speed to reach these thresholds than on-court players of the respective modalities. Soccer goalkeepers were superior in terms of these parameters when compared to futsal goalkeepers. No differences in VO2max or VT2 were observed between soccer and futsal on-court players, although soccer athletes reached the thresholds at higher speeds. In conclusion, soccer and futsal goalkeepers present lower aerobic capacity than on-court players. Soccer players show better performance in aerobic tests than futsal athletes